Modulating tiller formation in cereal crops by the signalling function of fertilizer nitrogen forms - Bernhard Bauer (Nature Portfolio, 2020)
Abstract Cereal crop yield comprises interrelated components, among which the number of tillers is highly responsive to nitrogen fertilization. We addressed the hypothesis of whether the supply of different nitrogen forms can be employed to manipulate the tiller number in cereal crops. Relative to urea or ammonium, exclusive supply of nitrate increased tiller number in hydroponically-grown barley plants. Thereby, tiller number correlated positively with the root-to-shoot translocation rate of endogenous cytokinins. External supply of a synthetic cytokinin analog further stimulated tillering in nitrate-containing but not in urea-containing nutrient solution. When the cytokinin analog 6-benzylaminopurine riboside was externally supplied to roots, its translocation to shoots was 2.5 times higher in presence of nitrate than in presence of urea or ammonium, suggesting that cytokinin loading into the xylem is affected by different nitrogen forms. We then translated this finding to field scale, cultivated winter wheat in four environments, and confirmed that nitrate fertilization significantly increased tiller number in a dose-dependent manner. As assessed in 22 winter wheat cultivars, nitrogen form-dependent tiller formation was subject to substantial genotypic variation. We conclude that cytokinin-mediated signaling effects of fertilizer nitrogen forms can be employed as a management tool to regulate the tiller number in cereal crops.